Data for: Riparian buffers mitigate downstream effects of clear-cutting on instream metabolic rates - Myrstener, Maria; Greenberg, Larry A.; Lidberg, William; Kuglerová, Lenka (Swedish University of Agricultural Sciences, 2025)
This dataset was used for the paper "Riparian buffers mitigate downstream effects of clear-cutting on instream metabolic rates". Data includes modelled whole stream oxygen data and modelled oxygen data from bottle incubations of biofilms, all modelled to gross primary production and respiration. This manuscript is part of a larger project which aims at evaluating how current forest management practices effect ecological functions of headwaters. This specific dataset was collected to answer if negative effects of clear-cutting on streams also propagate to downstream reaches.

Detta dataset samlades in och användes i artikeln "Riparian buffers mitigate downstream effects of clear-cutting on instream metabolic rates". Data inkluderar modellerat syredata från hela vattendraget samt modellerat syredata från flaskinkubationer av biofilmer, vilka alla har modellerats för att beräkna bruttoprimärproduktion och respiration. Detta manuskript är en del av ett större projekt som syftar till att utvärdera hur dagens skogsbruk påverkar ekologiska funktioner i källflöden (små bäckar). Detta specifika dataset samlades in för att undersöka om negativa effekter av kalavverkning på vattendrag även sprider sig till nedströms liggande sträckor.
Data tillhörandes: Kantzoner skyddar vattendragens primärproduktion och respiration mot nedströms effekter av kalhyggesbruk
Keywords: forest exploitation; skogsbruk; alga; alger; Land use; Markanvändning; algae; alger; buffer; kantzon; primary production; primärproduktion; forestry; skogsbruk; stream health; vattenkvalitet; Natural Sciences; Naturvetenskap; Environment; Miljö